HUBUNGAN KOMPLEKSITAS REGIMEN PENGOBATAN DENGAN KEPATUHAN PENGOBATAN PASIEN DIABETES MELITUS TIPE 2 DI POLI PENYAKIT DALAM RSUD SULTAN SURIANSYAH BANJARMASIN - Faqih, Muhammad; Alfian, Riza; Yumassik, Abdul Mahmud; Ilahi, Fitrah Shafran; Nordin, Nordin (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
Diabetes Mellitus (DM) is a chronic disease that requires prevention and treatment to reduce the various consequences associated with poor glycemic control. Diabetes mellitus treatment aims to control blood sugar levels within normal limits, improve the patient's quality of life, and prevent complications. One factor contributing to non-adherence to treatment in diabetes mellitus patients is the complexity of the medication regimen. This study aimed to examine the level of medication regimen complexity, medication adherence, and the relationship between medication regimen complexity and medication adherence in type 2 diabetes mellitus patients at the Internal Medicine Clinic of Sultan Suriansyah Hospital, Banjarmasin. This study used a cross-sectional design. Data were collected from August to September 2024, with 155 samples used in this study. The sampling method used a consecutive sampling technique. Medication regimen complexity (MRCI) data were obtained from prescriptions, while medication adherence data were collected using the Adherence to Refill Medication Scale (ARMS) questionnaire. The results of this study showed that the complexity of the patient's regimen was dominated by medications with a moderate level of complexity (75%, 48.4%). The results showed that the medication adherence rate was 61% of patients (39.4%). The correlation test showed an insignificant relationship between the complexity of the medication regimen and medication adherence, with a p value > 0.05 (0.139). Based on the research results, it can be concluded that the complexity of the medication regimen is not the main factor causing non-compliance in diabetes mellitus patients.